2014
DOI: 10.26634/jelt.4.2.2795
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Word (or World): Sexism in Philippine Preschool English Language Textbooks

Abstract: area of appearance, there are approved patterns for grooming, hairstyles, and clothing for the two sexes. Clothes that symbolize abilities to do things are regarded as appropriate for males and those that symbolize dependency and inability to walk long distances because

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
11
0
6
Order By: Relevance
“…Most of these studies focused on integrating a lived or person-based curriculum (Banegas & Velázquez, 2014 ; Norton & Pavlenko, 2004 ) that incorporates gender as part of a human’s identity and lived experiences. A number of researchers have also assessed gender representation in textbooks (Ariyanto, 2018 ; Curaming & Curaming, 2020 ; Lee & Mahmoudi-Gahrouei, 2020 ; Tarrayo, 2014 ). In terms of the teacher-perspective ELT, notable discussions have centered on the experiences of Argentinian student-teachers in incorporating the gender perspective in ELT (Banegas et al, 2019 ; Mojica & Castañeda-Peña, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies focused on integrating a lived or person-based curriculum (Banegas & Velázquez, 2014 ; Norton & Pavlenko, 2004 ) that incorporates gender as part of a human’s identity and lived experiences. A number of researchers have also assessed gender representation in textbooks (Ariyanto, 2018 ; Curaming & Curaming, 2020 ; Lee & Mahmoudi-Gahrouei, 2020 ; Tarrayo, 2014 ). In terms of the teacher-perspective ELT, notable discussions have centered on the experiences of Argentinian student-teachers in incorporating the gender perspective in ELT (Banegas et al, 2019 ; Mojica & Castañeda-Peña, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ELT in the Philippines, DepEd and CHED have yet to successfully remove the persistent misogynistic narratives ‘naturally’ hiding in textbooks (Curaming & Curaming, 2020 ; Tarrayo, 2014 ), curricula, and classroom discussions (Evangelista, 2017 ). Textbooks have been proven to be an important medium of cultural beliefs discussed between teachers and students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have found similar biases in English language textbooks for various dialects of English (e.g. Bergvall 1996;Lee & Collins 2010;Lewandowski 2014;Tarrayo 2014), and recently in example sentences in French journals (Richy & Burnett 2019). The issue has garnered some attention in recent LSA presentations (Boyce et al 2019;Haugen & Margaris 2020, as well as the 2018 panel Our Linguistics Community: Addressing bias, power dynamics, harrassment).…”
mentioning
confidence: 96%
“…This all proves that de-gendering of language due to gender-inclusivity is still at its high peak of special interest attracting the attention of linguists around the globe. Also, in the Philippine context, Tarrayo [10] argued that there is a crucial role expected among teachers in preventing gender discrimination from sneaking into the classroom.…”
mentioning
confidence: 99%